In silico structural analysis, physicochemical characterization and homology modeling of Arabidopsis thaliana Na+/H+ exchanger 2 protein - Das, Prateem (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.